(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2018)
Light weight concrete (LWC) found very similar properties and constructability with respect to normal concrete (NC). LWC was prepared using red clay (RC), sodium lauryl sulphate (SLS) and borax with the addition of waste materials like rice husk ash (RHA) and glass powder (GP) in aggregate composition. The compressive strength of NC and LWC found almost similar for seven, fourteen and twenty eight days with the inclusion of RHA and GP as the partial replacement of light weight aggregate in composition. Apparent porosity (AP) of LWC found slightly higher than the NC but the bulk density (BD) is about 13% lower than the NC. SLS (10% of water solution) was used as foaming agent. Borax (10% of water solution) might effect on hydration rate and temperature. The partial incorporation of GP and RHA in LWC lessen the thermal conductivity as compared to NC. Bangladesh J. Sci. Ind. Res.53(3), 225-232, 2018